Aubrey Williams: Abstraction in Diaspora - Kobena Mercer (British Art Studies, 2018)
Moving to London in 1952, Aubrey Williams gained valuable distance on the Amerindian petroglyphs that inspired his abstract painting. But as he deepened his engagement with the indigenous cultures of the precolonial Caribbean during the 1970s—working in studios in Jamaica and in Florida—Williams was edged out of late modernism’s narrative of abstraction. While retrospective exhibitions highlight the Olmec-Maya and Now series and the Shostakovich series produced during William’s circumatlantic journeys, both of which heighten abstraction as a medium of cross-cultural translation, the scholarship has left Williams isolated. Approaching Williams’s abstraction in the interpretive context of diasporic “ancestralism,” a distinctive framework addressing the diaspora’s unrecoverable past, I suggest his Amerindian focus is best understood in terms of a “hauntological” mode of abstraction critically responsive to the moment of decolonisation in which boundaries that once defined the national, the international, and the transnational were being thrown into crisis.